O-023 Asymptomatic intracranial hemorrhage after endovascular therapy for acute ischemic stroke is associated with worse outcomes. (16th November 2010) - Gupta, R; Nogueira, R; Jovin, T; Levy, E; Rai, A; Liebeskind, D; Hsu, D; Rymer, M; Zaidat, O; Tayal, A; Lin, R; Natarajan, S; et al.
Abstract : Background and purpose: The use of endovascular techniques to treat large artery occlusion in acute ischemic stroke has become more frequently employed as a treatment option. We sought to determine the predictors of intracranial hemorrhage after these procedures were performed. Methods: This is a retrospective review of data from 13 high volume stroke centers that perform endovascular treatments for acute ischemic stroke. Patients with anterior circulation strokes treated under 8 h from symptom onset with endovascular therapy were included. Hemorrhages were classified as parenchymal hematoma (PH) types 1 and 2 and hemorrhagic infarction (HI) types 1 and 2. Patients with PH bleeds were considered symptomatic and HI bleeds were asymptomatic. Binary logistic regression modeling was performed to determine the variables associated with symptomatic and asymptomatic hemorrhages after correcting for multiple comparisons. Results: A total of 1122 patients met the inclusion criterion for this study. Mean age for the cohort was 67±15 years with a median National Institutes of Health Stroke Scale (NIHSS) of 17 (IQR 13–20). The distribution for thrombus location at the initiation of endovascular therapy was as follows: M1 segment of the middle cerebral artery (MCA) 561 (50%), carotid terminus 214 (19%), M2 MCA 171 (15%), tandem occlusions 141 (13%) and isolated extracranial internal carotid artery occlusion 35 (3%). Parenchymal hematomas occurred in 96 (8.5%) patients and HI in 265 (24%) patients. There were no variables associated with symptomatic hemorrhages while the following variables were predictors of asymptomatic hemorrhage: diabetes mellitus (OR 2.02; 95% CI 1.46 to 2.79; p<0.0001), preprocedural use of intravenous tissue plasminogen activator (tPA) (OR 1.61, 95% CI 1.17 to 2.21; p<0.003), intra-arterial thrombolytic infusion (OR 1.52, 95% CI 1.09 to 2.10; p<0.01), higher baseline NIHSS (OR 1.032, 95% CI 1.001 to 1.06; p<0.04) and use of the Merci device (OR 1.71, 95% CI 1.18 to 2.48; p<0.003). After controlling for age, baseline NIHSS, recanalization status, PH, type of sedation and site of occlusion, the presence of asymptomatic hemorrhage was associated with a poor clinical outcome (OR 2.23, 1.53 to 3.23; p<0.0001). Conclusions: Diabetic patients and those who have been treated with intravenous tPA prior to the procedure or intraprocedural use of thrombolytics or the Merci device appear to be at a higher risk for asymptomatic hemorrhage. Moreover, patients with asymptomatic hemorrhage appear to be at a higher risk for a worse clinical outcome at the 90 day follow-up.